2010
DOI: 10.1163/092050609x12517858243706
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Release of Basic Fibroblast Growth Factor Using a Silk Fibroin Scaffold as Delivery Carrier

Abstract: Two different solvents were used to prepare two types of silk fibroin scaffolds via the salt-leaching technique, i.e., hexafluoroisopropanol (HFIP) and water. The in vitro release study suggests that the opposite charge between the silk fibroin and basic fibroblast growth factor (bFGF) at physiological pH rendered them to form a complex, and the difference in the solvents used to produce the silk fibroin scaffold did not affect the affinity of silk fibroin to bFGF. However, a higher degradation rate of the aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 55 publications
(74 reference statements)
1
17
0
Order By: Relevance
“…This degradation-controlled sustained drug release mechanism has been demonstrated in an in vitro model of basic fibroblast growth factor (bFGF) delivery from aqueous- and HFIP-derived silk scaffolds. In this study, release rates significantly increased with the addition of a proteolytic enzyme to the release medium, with the aqueous-based scaffolds demonstrating a higher increase in release rate due to a higher rate of degradation compared to the organic-derived scaffold [152]. Upon implantation in vivo , however, even though the silk scaffolds showed significant improvement in release duration compared to solution control, there was little difference in the degradation or bFGF release profile between the aqueous- and HFIP-derived silk scaffolds, likely due to the short study duration (26 days) not allowing for adequate degradation [152].…”
Section: Current State Of the Art In Sustained Drug Delivery Usingmentioning
confidence: 99%
“…This degradation-controlled sustained drug release mechanism has been demonstrated in an in vitro model of basic fibroblast growth factor (bFGF) delivery from aqueous- and HFIP-derived silk scaffolds. In this study, release rates significantly increased with the addition of a proteolytic enzyme to the release medium, with the aqueous-based scaffolds demonstrating a higher increase in release rate due to a higher rate of degradation compared to the organic-derived scaffold [152]. Upon implantation in vivo , however, even though the silk scaffolds showed significant improvement in release duration compared to solution control, there was little difference in the degradation or bFGF release profile between the aqueous- and HFIP-derived silk scaffolds, likely due to the short study duration (26 days) not allowing for adequate degradation [152].…”
Section: Current State Of the Art In Sustained Drug Delivery Usingmentioning
confidence: 99%
“…Natural polymers have the advantage of being rich in reactive chemical groups (hydroxyl, carboxyl, amide) which make them more hydrophilic and capable of interacting with bioactive molecules. Collagen and silk are examples of protein-based materials that have been functionalized through adsorption of bioactive molecules, including bone morphogenetic proteins (BMPs) [122, 123], basic fibroblast growth factor (bFGF) [124], vascular endothelial growth factor (VEGF) [125] and therapeutic compounds such as antibiotics [126] and heparin [127] as it is summarized in Table 2. In most of these studies the protein-based scaffolds were soaked in a solution containing the bioactive component.…”
Section: Techniques For the Functionalization Of Protein-based Biomentioning
confidence: 99%
“…The release of Rose Bengal as a model drug from human serum albumin nanoparticles is likely too slow to be practical, but the presence of trypsin accelerates the release rate of this encapsulated drug from nanoparticles (Lin et al, 2001). Wongpaint et al (2010) investigated the release of 125 I-labeled FGF-2 from silk fibroin scaffolds in nondegradation and degradation conditions using protease type XIV from Streptomyces griseus (EC 3.4.24.31). In non-degradation conditions, FGF-2 immediately diffused from the scaffold and gradually plateaued at a release fraction of about 30% after 24 h. However, in the presence of degradative enzymes, the initial burst release was 75.7%, and then the FGF-2 in the scaffold was gradually released until 89.0% was released by day 7.…”
Section: Fa Release From Sc Filmmentioning
confidence: 99%
“…FGF-2 can be bound to gelatin hydrogels by poly-ion complexation and its release controlled . Wongpaint et al (2010) suggested that FGF-2 release from silk fibroin scaffolds is sustained by ionic interactions between fibroin (pI: 3.8-4.5) and FGF-2 (pI 9.6). Furthermore, the release of epidermal growth factor from gelatin-based sponge, film, and ointment has also been investigated for wound healing (Okumura et al, 1990;Ulubayram et al, 2001).…”
Section: Fgf-2 Release From Sc Filmmentioning
confidence: 99%
See 1 more Smart Citation